Product life cycle modelling: A system dynamics approach / Norhafiza Mohd Noor - Mohd Noor, Norhafiza (2004)
Modelling in system dynamics is very useful as it deals with the changing processes involved in all social systems. This project as a whole is dealing with modelling product life cycles, specifically those of consumer durable products. The modelling task begins with the formation of flow diagram of the product life cycle. After that, the equations writing take place where the units on both sides must be equal to each other. Then, the structure of the model is transferred into the software based on the equations formulated earlier. Finally, the testing and validating tasks need to be done to ensure a good model. Throughout the project, we found that product life cycle modelling is very useful as it can be used to forecast sales, provided that the model built has includes all relevant factors. Furthermore, the use of the Bass diffusion theory is very useful, not only on this project, but also on other areas as well. The modelling task requires patience and hard work in order to create a model that reflects the real world. However, the use of the POWERSIM software in the system dynamics modelling makes the modelling task easier.